2002
DOI: 10.1023/a:1023004323444
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic distribution of Chlamydophila pneumoniae antibodies in a Malaysian population and possible correlation with coronary heart disease

Abstract: Chlamydophila pneumoniae, an important respiratory pathogen causing lower respiratory tract infections, has also been implicated in coronary heart disease (CHD). This study reports a cross-sectional, demographic, serological analysis of the prevalence of Chlamydophila pneumoniae antibodies in a multiracial Malaysian population. Generally, Malaysian Indians had the highest degree of seropositivity (58%) followed by the Chinese (54%) and the Malays (32%), results which were statistically significant (CI: 95%; p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Numerous studies have shown the salt sensitivity is heterogeneous among different populations [ 20 , 21 ]. While most research on hypertension has focused on some non-modifiable factors, such as sex [ 32 ], genes [ 33 , 34 ], and race [ 35 , 36 ], involvement of occupational disparities in the association between dietary salt intake and hypertension has been poorly investigated. Different OR patterns among occupations may reflect the importance of occupational mediation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown the salt sensitivity is heterogeneous among different populations [ 20 , 21 ]. While most research on hypertension has focused on some non-modifiable factors, such as sex [ 32 ], genes [ 33 , 34 ], and race [ 35 , 36 ], involvement of occupational disparities in the association between dietary salt intake and hypertension has been poorly investigated. Different OR patterns among occupations may reflect the importance of occupational mediation.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate for CHD was more than doubled between 1965 and 1991, from 24.6 per 100 000-57.2. Naidu et al (2003) in their research found that Malaysian Indians were more commonly afflicted with CHD. While Indians had been showing the highest CHD mortality rate so far, the rate among the Malays had been increasing most rapidly since 1970, concomitant with the latter's increase in their proportion of the urban population in peninsular Malaysia.…”
Section: Hypothesismentioning
confidence: 94%
“…15,16 Our work also demonstrates variation in seroprevalences according to race in United States dialysis patients. Further, the prevalence of some types of detected AVD events was lower among non-white patients than in Caucasians at enrollment, perhaps reflecting differential access to care or reporting biases prior to or early in ESRD, but race did not predict outcomes over observation.…”
Section: Racial Variation In Serological Markers Of Infection and Prementioning
confidence: 56%
“…Because the prevalence of C. pneumoniae and H. pylori exposure varies by geography and race, 15,16 we hypothesized that associations of chronic bacterial infections with atherosclerotic vascular disease and mortality may be quantitatively and/or qualitatively distinct among dialysis patients in the United States. We thus performed a cross-sectional and prospective study of a multiracial cohort of hemodialysis patients in northern California.…”
Section: Introductionmentioning
confidence: 99%